Prinsip-Prinsip Metode Dakwah Menurut Al-Quran - Aliyudin Aliyudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Da’wah method is one of dakwah system elements that having the urgent role and strategic for succesing da’wah. Da’wah method always develop and follow situation and condition of period. How ever The Holy Qur’an essentially gave foundation that related to the principles in creating varieties of da’wah method. This principle as revealed on an-Nahl: 125, they are al-Hikmah, al-Mauidzah hasanah and al-Mujadalah Ahsan. Then they are actualized by da’wah practice of Rasulullah SAW.